2011
DOI: 10.1148/radiol.11101557
|View full text |Cite
|
Sign up to set email alerts
|

Distal Aortic Intramural Hematoma: Clinical Importance of Focal Contrast Enhancement on CT Images

Abstract: Purpose:To investigate the prevalence, fate, and effect of focal contrast enhancement lesion within the hematoma on contrast material-enhanced computed tomographic (CT) images in patients with distal aortic intramural hematoma (IMH). Materials and Methods:This retrospective study was approved by the institutional review board; informed consent was waived. Clinical and CT data in 107 patients with distal IMH who received medical treatment were analyzed, including remodeling processes of IMH at follow-up CT. IMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 35 publications
(31 reference statements)
1
33
0
1
Order By: Relevance
“…Besides, 5 patients showed complete resorption of intimal defect. This finding was consistent with a previous study 16 showing variable remodeling processes of focal contrast enhancement within a hematoma in patients with distal IMH. Additional studies with a larger number of patients and longer follow-up are needed.…”
Section: Study Limitationssupporting
confidence: 94%
“…Besides, 5 patients showed complete resorption of intimal defect. This finding was consistent with a previous study 16 showing variable remodeling processes of focal contrast enhancement within a hematoma in patients with distal IMH. Additional studies with a larger number of patients and longer follow-up are needed.…”
Section: Study Limitationssupporting
confidence: 94%
“…IRAD data showed that, of 639 patients with type A acute aortic syndrome involving the ascending aorta, 23 (4%) showed intramural hematoma, while of 371 patients with type B acute aortic syndrome, 35 (9%) showed hematoma [10]. In our institution, the incidences of type A and B intramural hematoma were 28% (101/357) and 45% (159/350), respectively [11,13]. Thus, the incidence of intramural hematoma is much higher in Eastern countries.…”
Section: Schlüsselwörtermentioning
confidence: 56%
“…6). We have recently reported that this phenomenon is common in patients with distal intramural hematoma and is a risk factor for the development of localized aortic dissection during follow-up [13]. However, as hematoma resorption was the most common remodeling process and actually occurred in 70% of patients with focal contrast enhancement, early intervention during the acute stage is not necessary, and long-term imaging follow-up would be the best option (.…”
Section: Micro-intimal Tear Versus Rupture Of the Vasa Vasorum: Is Thmentioning
confidence: 99%
“…An ulcer-like projection (ULP) that occurs during the course of the complete thrombosis type [10,11] and a penetrating atherosclerotic ulcer (PAU) due to an arteriosclerotic ulcer [12,13] are conceptually different.ULP is an ulcerative projection image of the contrast medium that comparatively has a smooth outline and is a defect of the inner membrane continuous to the false lumen was condensed. Recently, ULP is treated as subtype (ULP type in aortic dissection) [1].…”
Section: Ulcer-like Projection In Aortic Dissectionmentioning
confidence: 99%